A Comparative Study Of Ultrasound Guided Pericapsular Nerve Group [Peng] Block Versus Suprainguinal Fascia Iliaca Compartment [Sifi] Block Using Ropivacaine In Patients With Fracture Femur For Reducing Pain Associated With Positioning For Subarachnoid Blo (International Journal of Environmental Sciences, 2025)
Femur fractures often require spinal anaesthesia for surgical management. Ultrasound-guided regional anaesthesia techniques such as Pericapsular Nerve Group (PENG) block and Suprainguinal Fascia Iliaca (SIFI) block offer alternative options for analgesia, but there is limited evidence comparing these methods in terms of pain relief and facilitating patient positioning for spinal anaesthesia .This study aims to compare the efficacy of PENG block and SIFI block with ropivacaine under ultrasound guidance in reducing pain and improving positioning for spinal anaesthesia in femur fracture surgeries.Aim : To compare the efficacy of the PENG block versus the SIFI block using ropivacaine in facilitating patient positioning for spinal anaesthesia in patients undergoing femur fracture surgeries.Methodology: A prospective, randomized controlled trial (RCT) conducted to compare the two ultrasound-guided regional anesthesia techniques at Adichunchanagiri Hospital and Research Centre, Department of Anaesthesiology. 60 adult patients aged 18-75 years, scheduled for elective femur fracture surgeries, with ASA physical status I or II, were randomly allocated into 30 each to receive either PENG block or SIFI block.Results: The mean age and weight of participants were comparable between the two groups. The onset of sensory block was significantly faster in Group P (4.77 minutes) compared to Group S (7.63 minutes, p = 0.012). Group P had superior post-block pain relief (VAS: 1.33 vs. 2.83, p = 0.034). The quality of spinal anesthesia positioning was better in Group P, with 76.2% achieving optimal positioning versus 23.8% in Group S (p = 0.008). Patients in Group P exhibited a higher level of satisfaction, with 81.8% satisfied, compared to 18.2% in Group S (p = 0.020). The time taken for patient positioning was also shorter in Group P (4.77 minutes vs. 5.94 minutes, p = 0.048). Hemodynamic parameters, such as heart rate and blood pressure, were similar between the two groups, although Group P had a significantly higher heart rate at 5 minutes post-block (80.17 bpm vs. 76.67 bpm, p = 0.002).Conclusion: The PENG block provided superior analgesia, facilitated easier patient positioning for spinal anesthesia, and resulted in higher patient satisfaction compared to the SIFI block in patients undergoing femur fracture surgeries. This study suggests that the PENG block is a more effective regional anesthesia technique for improving the perioperative experience in femur fracture surgeries.